Roof Covering Design Based on Bamboo - Salim, Muhammad Adib (Multidisciplinary Applied Research and Innovation, 2023)
In constructing a building, roof is one of the important structures that complete the building requirement. Materials such as tiles, ceramics and zinc are chosen by many people, but the cost for this kind of materials are quite expensive. Due to that, some people choose the cheap materials in the development of roof.. So, this study has been conducted to identify the significance of bamboo in order to solve this problem. The purpose of this project is to use bamboo as a material for a roof Hence, the bamboo is designed and the best method of curing has been reviewed.. Thus, bamboo can be used to replace other materials in constructing the bamboo. From those methods, the effectiveness of bamboo as the roof structure has been analysed. A questionnaire has been collected among the UTHM students and Pagoh residents. The limas roof design is chosem as the design of the roof for bamboo roof. As for the curing, boric acid and borac has been used in order to prevent the bamboo form the insects. Thus, the findings found that 80% of the responden agree that bamboo can be used as the roof structure. As a conclusion, the construction of bamboo based roof design can be adopted as one of the new innovations in Malaysian industries.